Bibliometric Mapping of Extended Reality (XR) in Education and Business Domains - Judijanto, Loso (The Eastasouth Journal of Information System and Computer Science, 2025)
This study presents a comprehensive bibliometric mapping of Extended Reality (XR) research in education and business domains, providing insights into thematic trends, collaborative networks, and emerging areas of interest. Using the Scopus database as the primary data source, publications from 2010 to 2025 were retrieved and analyzed exclusively with VOSviewer to generate keyword co-occurrence, author collaboration, country collaboration, temporal evolution, and density visualizations. The results reveal that virtual reality, augmented reality, extended reality, and engineering education are the most prominent and interconnected themes, with newer research increasingly focusing on metaverse, artificial intelligence, and Industry 4.0 integration. Co-authorship and country network maps show that the United States, Italy, Germany, and India are central hubs driving global research partnerships, while author collaborations cluster into specialized yet interconnected groups. The study highlights how education-oriented XR research emphasizes immersive learning, e-learning, and gamification, while business-focused studies target marketing innovation, customer engagement, and sustainability. These findings contribute to a holistic understanding of XR’s interdisciplinary evolution, offering strategic guidance for researchers, educators, industry leaders, and policymakers to foster innovation and cross-domain integration.